Delft Campus Of Schools - A Network Of Educational Offerings - Meyer, Sean (School of Architecture, Planning and Geomatics, 2020)
With a personal interest in youth, it became my primary point of departure, which acknowledges the fact that youth development within local income areas is hindered due to the lack and inadequate resources and spaces. The focus on youth is imperative to address social transformation and release them from the grip of poverty. Following on from my Honour year investigations of the youth as active agents in the urban environment, this Masters dissertation looks at youth development through an educational lens.